Controversial Aspects of the Subject of a Commercial Concession - N. A. Temnikova; A. A. Yuritsin (Сибирское юридическое обозрение, 2015)
The article deals with topical issues arising in the process of negotiation and performance of a commercial concession. The authors investigate law enforcement experience, norms of international law, theoretical studies regarding the ways of resolving the contradictions that arise.